The effect of different rotational speeds of a cylinder on Magnus wind turbine performance - Nasrallah, Siraj Abdulameer; Mohd Rafie, Azmin Shakrine (Praise Worthy Prize, 2022)
The current conditions of global technology are moving towards more renewable and sustainable energy, with each functional society completely dependent on electricity. Electricity has become fundamental in daily life. Wind is a vital green energy source that can be harvested naturally and sustainably, despite varying temperatures that occur due to the uneven solar heating of the Earth's surface. Therefore, this study has relied on unconventional wind turbines that aim to obtain largest possible energy from low wind speeds. In order to achieve this purpose, the experiment has required using of a different type of wind turbine, which is known as Magnus wind turbine. The Magnus effect involves utilizing rotating cylinder blades to harvest as much wind energy as possible, by generating aerodynamic forces perpendicular to the coming wind. Furthermore, most endeavors to increase the performance of wind turbines have followed traditional methods, in contrary to the bespoke method, which also consists of adding a support structure to the rotating cylinder in order to reduce cylinder vibration during rotation. However, there is not enough research on changing the cylinder rotation and the efficiency of the wind velocities at the low level. Based on this shortcoming, this study will provide information regarding the different speeds of cylinder rotation and the amount of power gained for each of them.